2018
DOI: 10.1101/355818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Children’s and Their Visitors’ Hand Hygiene Compliance

Abstract: 3 Background: Numerous interventions have tried to improve healthcare workers' hand 4 hygiene compliance, however little attention has been paid to children's and their visitors' 5 compliance. 6 Aim: To increase children's and visitors' compliance using interactive educational 7 interventions. 8Methods: This was an observational study of hand hygiene compliance before and after 9

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It is critical to improve the professional prevention and control knowledge of the paediatric patients' family and caregivers. Lary et al[ 21 ] showed that health education can improve the implementation rate of children’s hand hygiene, which is consistent with the results in our study[ 21 ]. Further investigation is needed on how to improve other professional prevention and control measures.…”
Section: Discussionsupporting
confidence: 93%
“…It is critical to improve the professional prevention and control knowledge of the paediatric patients' family and caregivers. Lary et al[ 21 ] showed that health education can improve the implementation rate of children’s hand hygiene, which is consistent with the results in our study[ 21 ]. Further investigation is needed on how to improve other professional prevention and control measures.…”
Section: Discussionsupporting
confidence: 93%
“…The study by Lary et al 14 is also at moderate risk of bias. Although the cluster randomized design was strong, minimal information was provided with respect to allocation procedures, baseline characteristics of participants, and potential for contamination.…”
Section: Risk Of Biasmentioning
confidence: 94%
“…Lary et al 14 implemented a cluster randomized controlled trial at a children's hospital in the United Kingdom. Six wards were randomized to one of two interventions or control.…”
Section: Studies Reporting Patient Hand Hygiene Ratesmentioning
confidence: 99%